INTERNATİONAL MİGRATİON AND AGRİCULTURAL SUSTAİNABİLİTY İN THE ÇUKUROVA REGİON: DETAİLED ANALYSİS OF SOCİO-ECONOMİC STRUCTURE AND MİGRATİON INTERACTİONS - Şinasi AKDEMIR; Ufuk GÜLTEKIN; Kasım Eren TUNA; Issaka Saidou ISMAILLA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This research aims to examine international migration movements and their effects on agricultural sustainability and the socio-economic structure in Turkey's Çukurova Region. The primary goal of the study is to provide strategic recommendations for the development of agricultural policies in the region by conducting a detailed analysis of the impacts of migration movements on agricultural sustainability. The first phase of the research was to investigate the general structure of international migration movements to the Çukurova Region and their socio-economic effects. In the second phase, data collected through surveys conducted with 4 family heads selected from the three most migration-receiving districts that represent the region in January and March 2024 was used. These surveys covered topics such as the migrants' countries of origin, family structures, capital transfers, sectors they work in, socio-economic statuses, and education levels. The collected data was evaluated using statistical and thematic analysis techniques, and these analyses provided a deep understanding of the dynamics of migration and their impacts on the agricultural sector. Findings reveal significant demographic shifts, with economic motivations driving migration decisions. The study points out the importance of understanding migrants' economic circumstances and cultural dynamics in shaping integration policies. Recommendations are proposed to facilitate economic integration and foster cultural harmony, contributing to a deeper understanding of migration's impact on agricultural sustainability.